Early rescue oocyte activation at 5 h post-ICSI is a useful strategy for avoiding unexpected fertilization failure and low fertilization in ICSI cycles - Xue, Lintao; Wang, Shikai; Wei, Pingpin; Liu, Haifang; Mao, Xianbao; Qin, Jie; Li, Yaoxuan; Zhang, Xiaohui; Li, Zhengda; Huang, Yueyue; Chen, Liangshi; Shi, Wen; et al. (Frontiers in Endocrinology, 2024)
Introduction Attempts to artificially activate unfertilized oocytes at 24 h post intracytoplasmic sperm injection (ICSI) have generally resulted in poor outcomes. This study aims to explore a new strategy for early judgement and rescue activation of unfertilized oocytes at 5 h post ICSI to avoid unexpected fertilization failure (UFF) or unexpected low fertilization (ULF) in ICSI cycles. Methods Firstly, time-lapse data from 278 ICSI cycles were retrospectively analyzed to establish an indicator for fertilization failure prediction. Secondly, 14 UFF and 20 ULF cycles were enrolled for an observational study, early rescue oocyte activation (EROA) was performed on oocytes without post-ICSI Pb2 extrusion to investigate fertilization efficiency, embryo development and clinical outcomes. Results The average time to Pb2 extrusion post-ICSI was 3.03±1.21 h, 95.54% of oocytes had extruded Pb2 before 5 h, and the sensitivity and specificity for monitoring Pb2 extrusion at 5 h by time-lapse imaging to predict fertilization were 99.59% and 99.78%, respectively. Early rescue activation of oocytes with no Pb2 extrusion resulted in acceptable fertilization and embryo developmental outcomes, in terms of the fertilization rate (75.00, 72.99%), 2PN fertilization rate (61.36, 56.93%), good-quality embryo rate (42.59, 50.00%), blastocyst formation rate (48.28, 46.03%), good-quality blastocyst rate (34.48, 33.33%), and oocyte utilization rate (36.36, 27.74%), for both UFF and ULF cycles. The clinical pregnancy, embryo implantation, and early miscarriage rates in the rescue oocyte activation group did not significantly differ from those in the Pb2 extrusion group. Fourteen unexpected fertilization failures and 20 low fertilization ICSI cycles were rescued and resulted in clinical pregnancy rates of 40.00% (4/10) and 57.14% (8/14), respectively. Conclusions This study demonstrates that monitoring Pb2 extrusion by time-lapse imaging can accurately predict fertilization outcomes, suggesting that early rescue oocyte activation at 5 h post ICSI is an effective strategy for avoiding unexpected fertilization failure and low fertilization in ICSI cycles.